Open Surgery for Hepatic Hydatid Disease - Sozuer, E; Akyuz, M; Akbulut, S (2014)
Hydatid disease is a zoonosis caused by the larvae of Echinococcus granulosus. Humans are an intermediate host and are usually infected by direct contact with dogs or indirectly by contaminated foods. Hydatid disease mainly involves the liver and lungs. The disease can be asymptomatic. Imaging techniques such as ultrasonography and computed tomography are used for diagnosis. The growth of hydatid cysts can lead to complications. Communication between bile duct and cysts is a common complication. The goal of treatment for hydatid disease is to eliminate the parasite with minimum morbidity and mortality. There are 3 treatment options: surgery, chemotherapy, and interventional procedures. Medical treatment has low cure and high recurrence rates. Percutaneous treatment can be performed in select cases. There are many surgical approaches for managing hydatid cysts, although there is no best surgical technique, and conservative and radical procedures are used. Conservative procedures are usually preferred in endemic areas and are easy to perform but are associated with high morbidity and recurrence rates. In these procedures, the parasite is sterilized using a scolicidal agent, and the cyst is evacuated. Radical procedures include hepatic resections and pericystectomy, which have high intraoperative risk and low recurrence rates. Radical procedures should be performed in hepatobiliary centers. The most common postoperative complications are biliary fistulas and cavity-related complications. Endoscopic retrograde cholangiopancreatography can be used to diagnose and treat biliary system complications. Endoscopic sphincterotomy, biliary stenting, and nasobiliary tube drainage are effective for treating postoperative biliary fistulas. C1 [Sozuer, Erdogan; Akyuz, Muhammet] Erciyes Univ, Fac Med, Dept Surg, Kayseri, Turkey. [Akbulut, Sami] Inonu Univ, Dept Surg, Fac Med, Malatya, Turkey. [Akbulut, Sami] Inonu Univ, Liver Transplant Inst, Fac Med, Malatya, Turkey.